Pengaruh Dimensi Experience Economy terhadap Augmented Reality Advertising Satisfaction dan Dimensi Behavioral Intention - Marilyn Tonapa; Kurniawati Kurniawati (Benefit: Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to analyze the effect of the Experience Economy dimension on Augmented Reality Advertising Satisfaction and Behavioral Intention Dimensions in online stores. This study uses primary data, the respondents in this study are people who have shopped online and have used the Augmented Reality feature. For the sample in this study using non-probability sampling technique with purposive sampling technique so that the sample used is as many as 230 respondents. Furthermore, the analytical tool used in this study is structural equation modeling (SEM) using the AMOS program. The empirical test results show that the Escapism dimension has the largest correlation value in influencing Augmented Reality Ad Satisfaction while Augmented Reality Ad Satisfaction has the largest correlation to Shopping Enjoyment and Shared Social Experience. Augmented Reality so that it can affect consumers' shopping enjoyment in online stores and can create an interesting atmosphere so that consumers want to share their shopping experience with their social community, this can affect purchase intention in online stores.